2020
DOI: 10.18662/po/11.2sup1/189
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experience of the World's Leading Countries in Inclusive Growth as Part of the Post-Industrial Economy: Challenges and Perspectives

Abstract: The main goal of the article is to study the experience of leading countries in the field of inclusive growth.The article considers the main prerequisites for the emergence of inclusive economic growth in the context of ensuring the interests of all segments of the population of the world community. The importance of introducing inclusive programs in the socioeconomic sphere of each country is substantiated as the main prerequisite for ensuring economic security, stability and the development of democratizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…40s XX century, when a society was created at Columbia University (USA), the goals of which were the study of the philosophical problems of education, the establishment of cooperation between philosophers and theorists of pedagogy, the development of training courses on the philosophy of education in colleges and universities, the training of personnel in this specialty, the philosophical examination of educational programs, etc. (Gontar et al, 2020).…”
Section: Problems Of the Formation Of The Philosophy Of Education In A Postmodern Societymentioning
confidence: 99%
“…40s XX century, when a society was created at Columbia University (USA), the goals of which were the study of the philosophical problems of education, the establishment of cooperation between philosophers and theorists of pedagogy, the development of training courses on the philosophy of education in colleges and universities, the training of personnel in this specialty, the philosophical examination of educational programs, etc. (Gontar et al, 2020).…”
Section: Problems Of the Formation Of The Philosophy Of Education In A Postmodern Societymentioning
confidence: 99%
“…Позитивний та негативний вплив, який визначаєть ся ефективністю стратегії використання інвестиційних коштів міжнародних організацій, а також від рівня роз виненості політичної та правової системи, інноваційності економіки та якості людського капіталу в країні. При бічники третьої групи [17] приходять до висновку, що міжнародна допомога за тих самих умов, у різних краї нах може демонструвати різні результати, залежно від:…”
Section: виклад основного матеріалуunclassified
“…The positive and negative impacts are determined by the effectiveness of the strategy for using investment funds of international organizations, as well as the level of development of the political and legal system, innovativeness of the economy, and the quality of human capital in the country (Pham & Pham, 2020). Proponents of the third group (Pham & Pham, 2020;Gontar et al, 2020) have concluded that international aid under the same conditions in different countries can demonstrate different results, depending on the circumstances of development domestic investment and the efficiency of use. The influence of globalization processes can contribute to the growth of the country's economy thanks to foreign investments and lead to divergence.…”
Section: Literature Reviewmentioning
confidence: 99%